Examining the Economic Impact of Cayenne Pepper in Traditional Markets of Makassar City: A Price Analysis Study - Pipi Diansari; Didi Rukmana; Wahyudi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
The price fluctuation of cayenne pepper has significant impacts on traders' cost performance and income. Therefore, determining the economic price for selling cayenne pepper is crucial. Economic price refers to the fair price for the sale of a commodity or product. This research aims to determine the economic price of cayenne pepper at Kalimbu Market in Makassar City, using 20 traders as respondents and primary data analysis. Cost analysis and break-even point techniques were employed to determine the basic price of cayenne pepper, followed by a switching value analysis to assess the percentage change in costs that could be tolerated. The study findings reveal that the economic price for kiosk cayenne pepper traders is Rp. 57,664/Kg, while the other economic price for kiosk cayenne pepper traders is Rp. 58,068/Kg. These results imply that the selling price set by the cayenne pepper trader is IDR 60,000, resulting in a small profit that is insufficient to meet the personal and family needs of traders.